An Overview on the Tribological Performance of Titanium Alloys with Surface Modifications for Biomedical Applications - Kaur, Sukhpreet; Ghadirinejad, Khashayar; H. Oskouei, Reza (Lubricants, 2019)
The need for metallic biomaterials will always remain high with their growing demand in joint replacement in the aging population. This creates need for the market and researchers to focus on the development and advancement of the biometals. Desirable characteristics such as excellent biocompatibility, high strength, comparable elastic modulus with bones, good corrosion resistance, and high wear resistance are the significant issues to address for medical implants, particularly load-bearing orthopedic implants. The widespread use of titanium alloys in biomedical implants create a big demand to identify and assess the behavior and performance of these alloys when used in the human body. Being the most commonly used metal alloy in the fabrication of medical implants, mainly because of its good biocompatibility and corrosion resistance together with its high strength to weight ratio, the tribological behavior of these alloys have always been an important subject for study. Titanium alloys with improved wear resistance will of course enhance the longevity of implants in the body. In this paper, tribological performance of titanium alloys (medical grades) is reviewed. Various methods of surface modifications employed for titanium alloys are also discussed in the context of wear behavior.